The Effect Of Using Image Media In Learning Literature On Increasing The Reading Interest Of Elementary Students 106810 Sampali Percut Sei Tuan - Simarmata, ATamara Tesalonika; Syafitri, Elsha; Tesalonika, Tesalonika; Ervia, Dea Vinni; Amin, Raja (Jurnal Pendidikan Indonesia, 2023)
The Influence of Using Picture Media in Literature Learning on Improving Reading Interest of Students at SD 106810 Sampali Percut Sei Tuan. Literature learning is often considered less interesting by elementary school students, which affects their reading interest. This study aims to determine the influence of using picture media in literature learning on improving reading interest of elementary school students. The method used is a quasi-experimental design with pretest-posttest control group design. The research sample consisted of 3 sixth- grade students taken using purposive sampling technique at SD 106810 Sampali Percut Sei Tuan. Data were obtained through reading interest tests and observations. The results showed that the use of picture media in literature learning had a significant effect on improving the reading interest of elementary school students (t = 5.26; p < 0.05). Therefore, it can be concluded that the use of picture media in literature learning can improve the reading interest of students at SD 106810 Sampali Percut Sei Tuan